2021
DOI: 10.1097/htr.0000000000000726
|View full text |Cite
|
Sign up to set email alerts
|

Research Letter: Concussion Knowledge Is Difficult to Predict From Self-Reported Exposure, Sports Participation, and Education

Abstract: Objectives: Increasing concussion knowledge could contribute to improving injury outcomes. Understanding the predictors of concussion knowledge could determine the areas of educational need. This study examined whether individual factors, prior brain injury, prior concussion education, and contact-sports participation predicted concussion knowledge. Design and Setting: Cross-sectional study with recruitment of community volunteers. Participants: An online survey was completed by 525 adults, 443 of whom provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…This study did not find sports fans to be less knowledgeable about concussion than nonsports fans. Indeed, both groups were relatively well-informed about concussion, as compared to prior reports (Kinmond et al, 2021); but misconceptions were still identified in the overall sample. This suggests that sports fans do not need a specific concussion education programme, but there is scope to address some of these misconceptions.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This study did not find sports fans to be less knowledgeable about concussion than nonsports fans. Indeed, both groups were relatively well-informed about concussion, as compared to prior reports (Kinmond et al, 2021); but misconceptions were still identified in the overall sample. This suggests that sports fans do not need a specific concussion education programme, but there is scope to address some of these misconceptions.…”
Section: Discussionmentioning
confidence: 69%
“…For this study, only the CKI and the VS were used. The RoCKAS was administered with minor changes to the item wording (see Kinmond et al, 2021). These changes followed advice for adaptations of the measure (i.e., retaining the original wording and adding the local term as a qualifier; Sullivan 2021).…”
Section: Concussion Knowledgementioning
confidence: 99%